An iterative algorithm for improving resolution and signal-to-noise ratio of captured noisy low-resolution diffraction fields - (:unkn) unknown (Optical Society of American (OSA), 2014)
An iterative super-resolution algorithm, based on capturing multiple noisy low-resolution diffraction fields, is proposed. It performs windowing on the reconstructed object to improve resolution and decrease noise level on captured fields. It provides satisfactory results. © 2014 OSA.